Intracranial control after Cyberknife radiosurgery to the resection bed for large brain metastases. Issue 1 (December 2015) - Vogel, Jennifer; Ojerholm, Eric; Hollander, Andrew; Briola, Cynthia; Mooij, Rob; Bieda, Michael; Kolker, James; Nagda, Suneel; Geiger, Geoffrey; Dorsey, Jay; Lustig, Robert; O'Rourke, Donald; et al.
Abstract Background Stereotactic radiosurgery (SRS) is an alternative to post-operative whole brain radiation therapy (WBRT) following resection of brain metastases. At our institution, CyberKnife (CK) is considered for local treatment of large cavities ≥2 cm. In this study, we aimed to evaluate patterns of failure and characterize patients best suited to treatment with this approach. Methods We retrospectively reviewed 30 patients treated with CK to 33 resection cavities ≥2 cm between 2011 and 2014. Patterns of intracranial failure were analyzed in 26 patients with post-treatment imaging. Survival was estimated by the Kaplan-Meier method and prognostic factors examined with log-rank test and Cox proportional hazards model. Results The most frequent histologies were lung (43 %) and breast (20 %). Median treatment volume was 25.1 cm3 (range 4.7–90.9 cm3 ) and median maximal postoperative cavity diameter was 3.8 cm (range 2.8–6.7). The most common treatment was 30 Gy in 5 fractions prescribed to the 75 % isodose line. Median follow up for the entire cohort was 9.5 months (range 1.0–34.3). Local failure developed in 7 treated cavities (24 %). Neither cavity volume nor CK treatment volume was associated with local failure. Distant brain failure occurred in 20 cases (62 %) at a median of 4.2 months. There were increased rates of distant failure in patients who initially presented with synchronous metastases (p = 0.02). Leptomeningeal carcinomatosis (LMC) developed in 9 cases, (34 %). Salvage WBRT was performed in 5 cases (17 %) at a median of 5.2 months from CK. Median overall survival was 10.1 months from treatment. Conclusions This study suggests that adjuvant CK is a reasonable strategy to achieve local control in large resection cavities. Patients with synchronous metastases at the time of CK may be at higher risk for distant brain failure. The majority of cases were spared or delayed WBRT with the use of local CK therapy.